Causas e consequências da dívida no cartão de crédito: uma análise multifatores - Kunkel, Franciele Inês Reis (2014)
The frightening growth of the number of Brazilian credit card users has generated concerns about the level of financial responsibility of those individuals in the use of the card. This work deals with this issue by seeking to assess the causes and consequences of credit card debt from behavioral factors. For this, we carried out a survey with 1.831 citizens users of credit card in the states of Rio Grande do Sul, Minas Gerais and Maranhão. As an instrument for data collection was used a structured questionnaire consisting by 114 questions, that addressed demographic variables, cultural variables, usage characteristics of credit card and seven behavioral factors - financial literacy, compulsive shopping, materialism, behavior of using of credit card, credit card debt, financial well -being and emotions. The analysis of the main model was based in the Structural Equation Modeling. Already the evaluation of the influence of demographic variables and characteristics of the credit card about the debt were measured by parametric hypothesis tests. The main results show that the presence of high levels of financial knowledge, attitudes and positive financial behaviors and the responsible use of the card reduce the probability of an individual incurring in credit card debt. On the other hand, the presence of materialistic behavior and compulsive consumption increases the probability of debt. As consequences of the debt, it was reported the lowest level of well-being and financial satisfaction and the presence of negative emotions and feelings. The descriptive statistics showed that respondents maintain responsible behavior in time to use the credit, are neither materialistic nor compulsive shoppers, contributing to low levels of debt checked on the credit card. The results of hypothesis tests bring to light that male individuals , young people , with dependent and with children, low education level, low income, who are unaware of the value of the interest rate paid in the event of use of revolving credit and who hold a greater number of credit cards are more likely to have credit card debts. These results are of interest in the financial sector and bodies with policy-making power. The work points to the need to provide citizens with information about the proper use of credit tools and develop on them the necessary financial skills for making responsible decisions keeping in mind the negative consequences experienced as a result of the debt.